NILAI SOSIAL BUDAYA DALAM LIRIK LAGU KERONCONG KARYA PAKSI BAND - Diana Nabilah; Tya Resta Fitriana (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
This research discusses the socio-cultural values reflected in the lyrics of the keroncong song by Paksi Band, which represents life in society. These values describe ideal behavior that is in line with the traditions and character of society. The aim of this research is to identify the socio-cultural values contained in the lyrics of Paksi Band's keroncong songs, describe them, and relate them to the realities of existing society. The data in this research was obtained through text documentation on a collection of relevant song lyrics, and analyzed using the Miles and Huberman interactive model. This research uses a qualitative descriptive method with a focus on socio-cultural values in the collection of Paksi Band keroncong song lyrics. The results of this research found 16 data related to socio-cultural values, consisting of 10 data regarding community values and norms, 1 data regarding cultural dynamics, 1 data regarding community dynamics, and 4 data related to societal system problems. It is hoped that further research can expand the study of socio-cultural values or analyze the more complex values contained in Paksi Band's songs. The theoretical implications of this research contribute to the development of the study of socio-cultural values in Paksi Band songs, which are part of Javanese literature and culture.